Microsoft Visual Basic 2008 : comprehensive - Shelly, Gary B.; Hoisington, Corinne (Singapore : Cengage Learning Asia Pte Ltd, 2011)
This Microsoft Visual Basic 20089 book utilizes an innovative step-by-step pedagogy, which integrates demonstration of professional-quality programs with in-depth discussions of programming concepts and techniques and opportunities for hands-on practice and reinforcement.
Chapter 1. Introduction to Visual Basic 2008 programming -- Chapter 2. Program and graphical user interface design -- Chapter 3. Program design and coding -- Chapter 4. Variables and arithmetic operations -- Chapter 5. Mobile applications using decision structures -- Chapter 6. Loop structures -- Chapter 7. Creating web applications -- Chapter 8. Using procedures and exception handling -- Chapter 9. Using arrays and file handling -- Chapter 10. Incorporating databases with ADO.NET -- Chapter 11. Multiple classes and inheritance -- Chapter 12. Cell phone applications and web services -- Enrichment Chapter. Visual Studio tools for office -- Appendixes -- Index.
Includes index.
Keywords: MICROSOFT VISUAL BASIC